The Oxford handbook of Spanish politics - Muro, Diego 1975-; Lago, Ignacio (Oxford University Press, 2020)
'The Oxford Handbook of Spanish Politics' provides a comprehensive and comparative overview of the Spanish political system through the lens of political science. This handbook examines Spanish politics and government since the transition to democracy. The volume studies the political history, institutional changes, bureaucratic decision-making, political behaviour, and foreign affairs of Spain. The introductory chapter provides an overview of the main themes of democratic Spain and discusses the end of Spanish exceptionalism. It also introduces Spanish politics to an international audience of scholars and practitioners to be considered either in its own right or as a case among others in a comparative perspective
Introduction - Diego Muro, Ignacio Lago -- - Political Institution in a Comparative Perspective - Josep M. Colomer -- - The 1978 Spanish Constitutional Design - Josep M. Vall es -- - Executive Politics in Spain - Juan Rodr iguez-Teruel -- - Legislative Politics in Spain - Bonnie N. Field -- - Multi-level Governance in Spain - Sandra Le on, Ignacio Jurado -- - Public Administration and its Problem-Solving Capacities - Salvador Parrado -- - Judicial Politics: The Constitutional Court - Nuno Garoupa, Pedro C. Magalh aes -- - The Spanish Army - Rafael Mart inez -- - The Quality of Democracy - Joan Font -- - Political Culture in Spain in the 21st Century - Mariano Torcal, Pablo Christmann -- - Spain in Comparative Perspective - Robert M. Fishman -- - Parties and Party Systems - M onica M endez Lago -- - Elections in Spain - Jos e Ram on Montero, Andr es Santana -- - Determinants of Voting Behaviour - Marta Fraile, Enrique Hern andez --
- The Spanish Electoral System - Agust i Bosch -- - Turnout - Pedro Riera -- - Interest Groups, Business Associations, and Trade Unions - Susana Aguilar -- - Migration Politics - Sergi Pardos-Prado -- - Social Movements - Eduardo Romanos -- - Spanish Nationalism Since 1975 - Xos e M. N u nez Seixas -- - Spanish Democratization Transition, Consolidation, and its Meaning in Contemporary Spain - Ignacio S anchez-Cuenca -- - Regional and National Identities in Spain - Mar ia Jos e Hierro -- - Public Policy and Policy-Making - Joan Subirats, Ricard Gom a -- - Welfare State - Elo isa del Pino -- - Social Inequalities - Leire Salazar -- - Economic Policy-Making in Contemporary Spain - Jos e Fern andez-Albertos -- - Employment Policy in Spain - Mariely L opez-Santana -- - Education Policy - H ector Cebolla-Boado -- - Gender Policy - T ania Verge -- - Corruption and Transparency - Manuel Villoria -- - Spanish Foreign Policy - Ram on Pacheco Pardo --
- The Political Uses of Forgetting in Spain - Omar G. Encarnaci on -- - Security and Defence Policy - F elix Arteaga -- - Spain in the EU - Ignacio Molina -- - Spain and Latin America - Andrea C. Bianculli -- - Europeanisation of Political Structures and Public Policies - Javier Arregui -- - Decentralization in Spain - C esar Colino -- - Terrorism in Spain - Diego Muro -- - Economic and Social Changes since the Restoration of Democracy - Miguel Requena -- - The Causes and Legacy of the Great Recession in Spain - Sebasti an Royo
Keywords: Geschichte 1975-2020; Politik; Politisches System; Spain / Politics and government / 1975-1982; Spain / Politics and government / 1982-; Spanien; Aufsatzsammlung